Debt maturity without commitment - Dirk Niepelt (Center for Economic Studies and ifo Institute (CESifo), 2008)
I analyze how lack of commitment affects the maturity structure of sovereign debt. Governments balance benefits of default induced redistribution and costs due to income losses in the wake of a default. Their choice of short- versus long-term debt affects default and rollover decisions by subsequent policy makers. The equilibrium maturity structure is shaped by revenue losses on inframarginal units of debt that reflect the price impact of these decisions. The model predicts an interior maturity structure with positive gross positions and a shortening of the maturity structure when debt issuance is high, output low, or a cross default more likely. These predictions are consistent with empirical evidence.
Keywords: E62; F34; H63; 330; Debt; maturity structure; no commitment; default; Öffentliche Anleihe; Laufzeit; Debt Management; Steuerpolitik; Kreditrisiko; Soziale Kosten; Theorie